On the nature of security - Jackson, M (AUT University, 2008)
In his On Adam’s House in Paradise, Joseph Rykwert traces successive engagements in the question of the origin of architecture as this question opens to the more primordial one of the origin of being human. Being human and the primitive hut, whether articulated by Vitruvius or Le Corbusier, have a complex and essential relation and one that opens a space for articulating an understanding of the meaning of ‘nature’ in whatever epoch or era. With this paper I aim to address Rykwert’s reference to Laugier’s Essay on Architecture and his understanding of the primitive hut. While Rykwert mentions that Laugier described himself as a philosophe, that is to say, associated with what we term the Physiocrats, the paper aims to amplify the significance of the French Physiocrats, particularly in the writings of François Quesnay, on the first systematic understanding of what we now call economics. It is not simply that this invention of economics held that all wealth derived from nature, from cultivation and the land, to the extreme exclusion of manufacture as a source of wealth. Nor is it simply that this economics held the fundamental productive unit to be the family. In both of these we would simply see Laugier’s quaint image of the primitive hut as an all too literal manifestation of physiocratic economy. Rather, with Quesnay, a new horizon of an understanding of the human emerges, one that displaces the rule of Mercantilism that had dominated the 17th century, and that relocates the essential nature of the human. There develops, in the 18th century, a new term for understanding precisely what seems to escape the sovereign exercise of power. That term is ‘population.’ This paper will critically assay the extent to which a bifurcation in an understanding of territory, power and sovereignty, that revolves around the human as subject and as population, opens a radical engagement with Laugier’s understanding of ‘origins,’ impacting on the discourse of origins in architecture that unfolds in modernity. Particular reference will be made to Michel Foucault’s 1977-78 lectures at the College de France, Security, Territory, Population.